A phosphorylation map of the bovine papillomavirus E1 helicase - Lentz, Michael R (BioMed Central, 2006)
BACKGROUND: Papillomaviruses undergo a complex life cycle requiring regulated DNA replication. The papillomavirus E1 helicase is essential for viral DNA replication and plays a key role in controlling viral genome copy number. The E1 helicase is regulated at least in part by protein phosphorylation, however no systematic approach to phosphate site mapping has been attempted. We have utilized mass spectrometry of purified bovine papillomavirus E1 protein to identify and characterize new sites of phosphorylation. RESULTS: Mass spectrometry and in silico sequence analysis were used to identify phosphate sites on the BPV E1 protein and kinases that may recognize these sites. Five new and two previously known phosphorylation sites were identified. A phosphate site map was created and used to develop a general model for the role of phosphorylation in E1 function. CONCLUSION: Mass spectrometric analysis identified seven phosphorylated amino acids on the BPV E1 protein. Taken with three previously identified sites, there are at least ten phosphoamino acids on BPV E1. A number of kinases were identified by sequence analysis that could potentially phosphorylate E1 at the identified positions. Several of these kinases have known roles in regulating cell cycle progression. A BPV E1 phosphate map and a discussion of the possible role of phosphorylation in E1 function are presented.